STUDI KASUS DESAIN MATRIX ACIDIZING DENGAN MEMPERHATIKAN MEKANISME PEMBENTUKAN WORMHOLE PADA RESERVOIR KARBONAT - Praditya Nugraha; Leonardo Davinci Massolo; Nur Wahyuni (INTAN Jurnal Penelitian Tambang, 2019)
This paper discusses the comparison of acid calculation required on carbonate matrix acidizing between volumetric method and by considering the wormhole formation mechanism. Normally the standard estimation of the required acid volume in carbonate rocks is based on volumetric method where the acid will be distributed evenly to all direction in the targeted formation. However the real acid mechanism at carbonate rock is affected by the creation of wormhole. This case study compares the amount of acid volume to both scenarios. The result shows more optimistic result for volumetric method compared to the wormhole influences.